Automated Z-Score Based Nutritional Status Classification for Children Under Two Using Smart Sensor System - Yunidar Yunidar; Melinda Melinda; Rina Ridara; Nurlida Basir (Poltekkes Kemenkes Surabaya, 2026)
Non-Indexed Publication